2016
DOI: 10.1371/journal.pntd.0005261
|View full text |Cite
|
Sign up to set email alerts
|

Former Buruli Ulcer Patients’ Experiences and Wishes May Serve as a Guide to Further Improve Buruli Ulcer Management

Abstract: BackgroundBuruli ulcer (BU), caused by Mycobacterium ulcerans, is a neglected tropical disease frequently leading to permanent disabilities. The ulcers are treated with rifampicin and streptomycin, wound care and, if necessary surgical intervention. Professionals have exclusively shaped the research agenda concerning management and control, while patients’ perspective on priorities and preferences have not explicitly been explored or addressed.Methodology/Principal findingsTo get insight into patient perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…16 This study addressed a question that was also deemed important by former patients who prioritised research into treatment that avoided painful injections and had few sideeffects. 28 Age and sex distribution, as well as socioeconomic status and educational level in this study population were all typical for the population affected by Buruli ulcer in west Africa.…”
Section: Discussionmentioning
confidence: 56%
“…16 This study addressed a question that was also deemed important by former patients who prioritised research into treatment that avoided painful injections and had few sideeffects. 28 Age and sex distribution, as well as socioeconomic status and educational level in this study population were all typical for the population affected by Buruli ulcer in west Africa.…”
Section: Discussionmentioning
confidence: 56%
“…Good wound management is required not only for faster and sequelae-free epithelialization of ulcers but also for increased quality of life of patients. BU lesions were previously noticed to be associated with no or limited pain, but recent studies have revealed that many patients actually experience pain after the start of treatment [ 72 , 95 , 96 ]. This pain is most felt during wound dressing change when in many settings, gauze is the only dressing type being used [ 97 ].…”
Section: Importance Of Wound Management In Buruli Ulcermentioning
confidence: 99%
“…Shorter treatment would benefit patients by reducing indirect costs and barriers to treatment, and increasing adherence (9, 10, 32). With RIF, a clear dose-response relationship was demonstrated by linear regression with both clinical (swelling grade) and microbiological (CFU) outcome.…”
Section: Discussionmentioning
confidence: 99%